Psychiatric disorders among the children of 5 to 18 years old of 'SIDR' affected areas (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Natural disasters give raise a significant amount of physical and mental impairment in human beings. Any sort of disaster acts as a causative and maintaining factor for any psychiatric morbidity. In November 15, 2007, the cyclone "SIDR" intensified to reach peak winds of 215 km/h (135 mph) according to the IMD, a peak of 250 km/h (155 mph) according to the JTWC. "SIDR" officially made landfall around 1700 UTC later that day, with sustained winds of 215 km/h (135 mph). As it intensified to a Category 4-equivalent cyclone and thus coastal districts of Bangladesh faced heavy rainfall as an early impact of the cyclone. The damage in Bangladesh was extensive, including tin shacks flattened, houses and schools blown away and enormous tree damage. The entire cities of Patuakhali, Barguna and Jhalokati District were hit hard by the storm surge of over 5 meters ( 16 ft). The head of the Red Crescent in Bangladesh expects the death toll to reach as high as 10,000. Over 3,000 other fishermen were reported missing on over 500 fishing boats. The "SIDR" left its strong impact on those who survived. Objectives: The Study was aimed to estimate the prevalence of psychiatric disorder among children and adolescents in the "SIDR" affected areas. Method: This was cross sectional, qualitative study done among the children and adolescent groups of 5 to 18 years old to see the effect of natural disaster on the people of southern part of Bangladesh. The whole of the children population who attended in the health camp were included in the study during the study period. Three teams have worked among the four "SIDR" affected districts. Each team consists of Psychiatrists, General Physicians, and Clinical Psychologist.Results: A total of 158 children in four defined areas revealed that the prevalence rate of psychiatric disorder was 48%.Conclusion: This type of study should be done in multi-centers in SIDR affected disti.icts of Bangladesh to find out the actual prevalence rate of child and adolescent psychiatric disorder.